Community pharmacies: Key players in point-of-care diagnostics for STI screening in Africa. - Agnes N Kiragga; Annet Onzia; Vivian Nakate; Irene Bagaya; Evelyn Natuha; Emmanuel Mande; Olivia Kataike; Rosalind Parkes-Ratanshi; Matthew M Hamill; Yukari C Manabe (PLoS ONE)
Background Sexually Transmitted Infections (STIs) rank in the top 5 disease categories for which adults in developing countries seek healthcare services. Community pharmacies offer clients convenience, proximity, extended opening hours, privacy, and efficiency, which could make them desirable locations for HIV and STI screening and treatment. We examined the feasibility of using point-of-care (POC) STI tests for screening HIV and other STIs at community pharmacies. Methods We conducted a prospective cohort study of persons seeking medication and other services at 18 purposively selected community pharmacies in Kampala, Uganda. Study participants comprised two broad categories: i) Symptomatic persons aged 18 years who presented with at least one STI sign or symptom and were purchasing treatment for themselves; ii) persons presenting with no STI symptom who had come to purchase any other medication, including family planning services such as emergency contraception. POC tests were used to test HIV, Chlamydia trachomatis (Ct), Neisseria gonorrhoeae (Ng), Trichomonas vaginalis (Tv), and Syphilis. Test results were returned on-site or via telephone within 48 to 72 hours. Descriptive statistics were used to estimate the prevalence of STIs. Results Of the 450 participants enrolled, 235 (52.2%) were symptomatic, 215 (47.8%) were asymptomatic, and 280 (62.2%) were females. STI testing was feasible, with an acceptability rate of 99.8%. 135 (30%) of participants had at least one STI; HIV prevalence was 39 (8.7%), Syphilis prevalence was 14 (3.1%), 50 (11.1%) tested positive for Ng, 39 (8.7%) were positive for Ct while. The prevalence of Tv was 25 (8.9%) (tested among women). A total of 107 (23.8%) participants had used an antibiotic in the preceding month. Conclusion Our research underscores the potentially pivotal role of community pharmacies in deploying POC diagnostics for STIs and antimicrobial stewardship by decreasing unnecessary antibiotic dispensation across Africa.